Flexible band versus rigid ring annuloplasty for tricuspid regurgitation: a systematic review and meta-analysis - Wang, Nelson (Ann Cardiothorac Surg, 2017)
BACKGROUND: Up to 20% of patients have pre-discharge residual moderate to severe tricuspid regurgitation (TR) after tricuspid repair. Reoperations for recurrent TR carry high mortality rates, which emphasizes the importance of identifying the optimal technique for the surgical management of TR. The present study is a systematic review and meta-analysis that aims to compare short and long term survival and freedom from TR of flexible band ring versus rigid ring for annuloplasty of TR. METHODS: We conducted a systematic review and meta-analysis of comparative studies to evaluate these procedures. A systematic search of the literature was performed from six electronic databases. Pooled meta-analysis was conducted using odds ratio (OR) and weighted mean difference (WMD). RESULTS: The rates of in-hospital mortality were not different between the two groups, with cumulative rates of 6.9% for flexible band and 7.3% for rigid ring (OR: 0.92; 95% CI: 0.49–1.71). Rates of stroke were also similar with 1.7% of flexible band and 1.3% of rigid rings suffering a perioperative stroke (OR: 1.29; 95% CI: 0.74–2.23). Rigid ring had significantly better freedom from grade ≥2 TR at 5 years (OR: 0.44; 95% CI: 0.20–0.99) and overall (P=0.005). There was no significant difference in overall rates of reoperation (P=0.232) and survival (P=0.086) between flexible band and rigid ring. CONCLUSIONS: Both rigid ring and flexible band offer acceptable outcomes for the treatment of TR. Compared to flexible band, rates of TR are stable after rigid ring annuloplasty and long term freedom from TR are superior for rigid ring devices. Large prospective randomized trials are required in order to validate these findings and assess for improvements in patient survival.